Resolution of Abfraction-Associated Gingival Fenestration Utilizing Connective Tissue Grafting - Braydon Haskell; J. Kobi Stern; Jordan Ghiassi; Andrew Kurialacherry; Sadja Gaud-Quintana; Mark E. Peacock (Case Reports in Dentistry)
Introduction. Gingival fenestration (GF) is a distinct clinical entity of uncertain etiology that is seldom documented in the literature. It has been associated mainly with submucosal mechanical irritants such as calculus that subsequently create an opening in the oral soft tissue, usually at facial anterior sites. Surgical correction may be indicated to address functional and/or esthetic concerns. Case Presentation. The patient, a 74-year-old male, presented to the clinic with a chief complaint of “something is poking through my gum.” Clinical exam revealed a gingival fenestration on the facial of tooth #11, associated with what appeared to be a pronounced noncarious cervical lesion (NCCL). Surgical treatment consisted of a connective tissue graft and odontoplasty of the sharp protruding edge of the root surface. Healing was uneventful with excellent closure of the fenestration and no evidence of recurrence after 18 months of follow-up. Conclusion. GF is a perforation of the mucosa typically associated with underlying sharp mechanical etiology. This report describes a fenestration that developed from a probable abfractive lesion, which later was successfully closed and exhibits long-term stability.